TRIM5α Restricts Flavivirus Replication by Targeting the Viral Protease for Proteasomal Degradation - Chiramel, Abhilash I.; Meyerson, Nicholas R.; McNally, Kristin L.; Broeckel, Rebecca M.; Montoya, Vanessa R.; Méndez-Solís, Omayra; Robertson, Shelly J.; Sturdevant, Gail L.; Lubick, Kirk J.; Nair, Vinod; Youseff, Brian H.; Ireland, Robin M.; et al. (Cell reports (Cambridge), 2019)
Tripartite motif-containing protein 5α (TRIM5α) is a cellular antiviral restriction factor that prevents early events in retrovirus replication. The activity of TRIM5α is thought to be limited to retroviruses as a result of highly specific interactions with capsid lattices. In contrast to this current understanding, we show that both human and rhesus macaque TRIM5α suppress replication of specific flaviviruses. Multiple viruses in the tick-borne encephalitis complex are sensitive to TRIM5α-dependent restriction, but mosquito-borne flaviviruses, including yellow fever, dengue, and Zika viruses, are resistant. TRIM5α suppresses replication by binding to the viral protease NS2B/3 to promote its K48-linked ubiquitination and proteasomal degradation. Importantly, TRIM5α contributes to the antiviral function of IFN-I against sensitive flaviviruses in human cells. Thus, TRIM5α possesses remarkable plasticity in the recognition of diverse virus families, with the potential to influence human susceptibility to emerging flaviviruses of global concern.